Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Revealing changes in the microbiome of Symbiodiniaceae under thermal stress - Emma F. Camp; Tim Kahlke; Matthew R. Nitschke; Deepa Varkey; Nerissa L. Fisher; Lisa Fujise; Samantha Goyen; David J. Hughes; Caitlin A. Lawson; Mickael Ros; Stephen Woodcock; Kun Xiao; et al. (Environmental Microbiology, 2020)
Summary Symbiodiniaceae are a diverse family of marine dinoflagellates, well known as coral endosymbionts. Isolation and in vitro culture of Symbiodiniaceae strains for physiological studies is a widely adopted tool, especially in the context of understanding how environmental stress perturbs Symbiodiniaceae cell functioning. While the bacterial microbiomes of corals often correlate with coral health, the bacterial communities co‐cultured with Symbiodiniaceae isolates have been largely overlooked, despite the potential of bacteria to significantly influence the emergent physiological properties of Symbiodiniaceae cultures. We examined the physiological response to heat stress by Symbiodiniaceae isolates (spanning three genera) with well‐described thermal tolerances, and combined these observations with matched changes in bacterial composition and abundance through 16S rRNA metabarcoding. Under thermal stress, there were Symbiodiniaceae strain‐specific changes in maximum quantum yield of photosystem II (proxy for health) and growth rates that were accompanied by changes in the relative abundance of multiple Symbiodiniaceae‐specific bacteria. However, there were no Symbiodiniaceae‐independent signatures of bacterial community reorganisation under heat stress. Notably, the thermally tolerant Durusdinium trenchii (ITS2 major profile D1a) had the most stable bacterial community under heat stress. Ultimately, this study highlights the complexity of Symbiodiniaceae‐bacteria interactions and provides a first step towards uncoupling their relative contributions towards Symbiodiniaceae physiological functioning.

Congo Basin peatlands: threats and conservation priorities - Greta C. Dargie; Ian T. Lawson; Tim J. Rayden; Lera Miles; Edward T. A. Mitchard; Susan E. Page; Yannick E. Bocko; Suspense A. Ifo; Simon L. Lewis (Mitigation and Adaptation Strategies for Global Change, 2019)

Environmental influences on stem borer incidence in Australian subtropical Corymbia plantations - Valerie J. Debuse; Tim E. Smith; Chris T. Holloway; Aaron N. Wiegand; Helen F. Nahrung; Simon A. Lawson (Journal of Pest Science, 2019)

Just a FAD ? Ecosystem impacts of tuna purse‐seine fishing associated with fish aggregating devices in the western Pacific Warm Pool Province - Shane P. Griffiths; Valerie Allain; Simon D. Hoyle; Tim A. Lawson; Simon J. Nicol (Fisheries Oceanography, 2019)
The western and central Pacific Ocean supports the world's largest tuna fisheries. Since the 1990s, the purse‐seine fishery has increasingly fished in association with fish aggregating devices ( FAD s), which has increased catches of juvenile bigeye and yellowfin tunas and vulnerable bycatch species (e.g., sharks). This has raised concerns regarding the sustainability of these species’ populations and the supporting ecosystem, but may provide improved food security of Pacific Island nations through utilisation of FAD ‐associated byproduct species (e.g., wahoo). An ecosystem model of the western Pacific Warm Pool Province was used to explore the potential ecological impacts of varying FAD fishing effort (±50% or 100%) over 30 years. The ecosystem has undergone a significant change in structure since 1980 from heavy exploitation of top predators (e.g., tunas) and “fishing up the food web” of high‐trophic‐level non‐target species. The ecosystem appeared resistant to simulated fishing perturbations, with only modest changes ( FAD effort by at least 50% was predicted to increase the biomass of tuna species and sharks and return the ecosystem structure to a pre‐industrial‐fishing state within 10 years. Spatial disaggregation of the model and integration of economic information are recommended to better capture ecological and economic changes that may result from fishing and/or climate impacts and to develop appropriate management measures in response.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

International workshop on opportunities for ecosystem approaches to fisheries management in the Pacific Ocean tuna fisheries - Valerie Allain; Simon Nicol; Jeffrey Polovina; Marta Coll; Robert Olson; Shane Griffiths; Jeffrey Dambacher; Jock Young; Jesus Jurado Molina; Simon Hoyle; Tim Lawson (Reviews in Fish Biology and Fisheries, 2012)